PERSONAL LIBRARY OF PROFESSOR VANDA STONIENĖ - TARASKEVIČIŪTĖ, EGLĖ (Knygotyra, 2013)
Professor Vanda Stonienė (1932–2008) was not only a scientist of Vilnius University, but also she had a deep interest in books at home. She gathered a personal scientific library which was used in her work. The library contains 379 pieces. The professor`s personal library mainly includes periodicals and books, but also other materials such as personal artefacts are found in the collection. Another, family-type, shared library exists at home of V. Stonienė, but for her it was only an additional source of information used to enrich and complement her knowledge. An analysis and interpretation of all the pieces of her personal library are presented in this article. All the material was clasified according to the lingual, thematical, quantative, and chronological principles. The classification met the requirements of the Universal Decimal Classification (UDC). The overview of the personal library of V. Stonienė made it possible to better understand her personality, principles of work and life.